Diverse migration tactics of fishes within the large tropical Mekong River system. (2nd June 2022) - Vu, An V.; Baumgartner, Lee J.; Mallen‐Cooper, Martin; Doran, Gregory S.; Limburg, Karin E.; Gillanders, Bronwyn M.; Thiem, Jason D.; Howitt, Julia A.; Kewish, Cameron M.; Reinhardt, Juliane; Cowx, Ian G.
Abstract: Fish often migrate to feed, reproduce and seek refuge from predators and prevailing environmental conditions. As a result, migration tactics often vary among species based on a diversity of life history needs, although variation within species is increasingly being recognised as important to population resilience. In this study, within‐ and among‐species diversity in life history migratory tactics of six Mekong fish genera was examined using otolith microchemistry to explore diadromous and potamodromous traits. Two species were catadromous and one species was an estuarine resident, while the remaining three species were facultative in their migration strategies, with up to four tactics within a single species. Migrant and resident contingents co‐existed within the same species. Management, conservation and mitigation strategies that maintain connectivity in large tropical rivers, such as effective fishway design, should consider a diversity of migration tactics at the individual level for improved outcomes.